Activating transcription factor 3 inhibits NF‑κB p65 signaling pathway and mediates apoptosis and cell cycle arrest in cervical cancer cells - Amirhossein Akbarpour Arsanjani; Haniyeh Abuei; Abbas Behzad-Behbahani; Zahra Bagheri; Rita Arabsolghar; Ali Farhadi (Infectious Agents and Cancer, 2022)
Abstract Background As a novel tumor suppressor mediator, activating transcription factor 3 (ATF3) has recently aroused an interest in its possible therapeutic applications in various cancers. In this study, we evaluated the effect of ATF3 overexpression on the cellular level of nuclear factor kappa B (NF-κB) in human papillomavirus (HPV)-infected Ca Ski cells. Further, we examined whether ATF3 could mediate cell cycle arrest and alter the apoptosis level of Ca Ski cells. Methods The biological behavior of Ca Ski cells was evaluated prior and subsequent to the overexpression of ATF3 by MTT assay, fluorescence microscopy, cell cycle and annexin V/PI flow cytometric analysis. The effect of ectopic ATF3 expression on the cellular level of NF-κB in HPV-positive cells was evaluated by western blotting assay. Results The overexpression of ATF3 in Ca Ski cells led to significant apoptosis and cell cycle arrest in the G1 phase. Western blotting assay revealed a discernible reduction of NF-κB p65 level in cervical cancer cells. Conclusion ATF3 acts as a tumor suppressor factor in HPV16-infected Ca Ski cells and exerts anti-cancer effects on HPV16-related cervical cancer cells potentially by hindering cell growth and inducing cell cycle arrest through the down-regulation of NF-κB. Our results suggest that ATF3 induction or NF-κB suppression may be useful targets for HPV16-related cervical cancer prevention and treatment.